Chamberlain Bridge. Barbados, B. W. I. - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2023)
A picturesque scene of the Chamberlain Bridge. Barbados, B.W.I. Boats are seen docked in the water near the bridge. In the foreground the Parliament Building and the clock tower are seen. There are a number of people gathered on the bridge. There is a small image pocket entitled – KODAK AS YOU GO KNIGHT’S LTD. Within this pocket are ten small images of the following, starting from the top: The Wharf. Barbados, B.W.I. Government House. Barbados. B.W.I. Milk Market, Barbados, B.W.I. Public Market. Barbados, BW.I. Avenue to Codrington College. Barbados, B.W.I. Carting Canes at Factory. Barbados, B.W.I. Canes in Arrow and Native Labourers. Barbados. B.W.I. Round Rock Bathsheba, Barbados, B.W.I. Crane Coast. Barbados. B.W.I. This is a divided back postcard. Back of the postcard ME HTP. £30 RF. Published by Knight’s Ltd.
Landscape; Colour; 3 ½” x 5 ½”
Keywords: Bridges; Swing Bridges; Boats; Parliament Building; Historic Buildings; Piers and wharves; Chamberlain Bridge; Clock Tower; Careenage